Effect Of Spiritual Emotional Freedom Technique (SEFT) On The Decrease In Anxiety Levels In Cancer Patients - Dewi Musfira Hasal; Muriyati; Nadia Alfira (Comprehensive Health Care, 2021)
According to WHO 2013 data, every year the number of cancer patients in the world increases, the incidence of cancer is increasing from 12.7 million cases in 2008 to 14.1 million cases of 2012. The diagnosis of cancer is daunting for the patient and can affect the patient's psychological conditions especially anxiety. This anxiety is common because of the financial problems, diseases of symptoms, concerns about healing, concerns that can not run function as humans maximally, and may affect the prognosis of disease that should be good, but becomes otherwise. The harassment of nonfarmochalate anxiety is by distraction and relaxation one of them is a Left. This study aims to determine the effect of theft of left therapy on the decline of anxiety in cancer patients. Research methods using experimental pre-design by using the type of One Group Pre-test post-test design, with purposive sample technique and using the t-paired test of Wilcoxon test alternative. The results of the research obtained that the level of anxiety of respondents before the soft therapy is the average anxiety is as much as 11 people (73.3%). While the rate of anxiety of respondents after the seft therapy is the average of lightweight anxiety as many as 14 people (93.3%). From the results of the Wilcoxon test is obtained there is the effect of giving the seft to the decrease in anxiety level in cancer patients with value ρ value = 0,002 (ρ <0.05). The conclusion of this research is there is an enhanced influence between the spiritual therapy of the Emotional Freedom Technique (Seft) to the decline in anxiety level in cancer patients at Griya Al-Afiat clinics.